Supportive Learning Tool for Electrical Machines Laboratory Using Video Clips - Somboon Nuchprayoon (2018)
© Published under licence by IOP Publishing Ltd. Electrical machines and electromechanical energy conversion serve as required course in most undergraduate programs in power engineering around the globe. Sophomore and junior students should attend both lecture and laboratory sessions to gain basic foundation in power engineering. The Department of Electrical Engineering, Faculty of Engineering, Chiang Mai University, Thailand, has made video clips for electrical machines laboratory and uploaded to YouTube. The main objectives of the video clips are to enable the students to review the laboratory session at their leisure time and to improve their laboratory skills. Upon completion, the students were pleased and found that the video clips were helpful.